A Conversational Analysis of Racial Humors Targeting Chinese Characters in “Family Guy” - Syakir, Mochammad Fauzan; Nurfa'ida, Reza; Faiqiah, Nur Layli (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2025)
This research article examines the use of racial humor targeting Chinese characters in the television series "Family Guy" through conversational analysis. Contextualization cues, linguistic features, paralinguistic signals, non-verbal communication, and visual elements are analyzed across five selected clips. The study contextualizes each scene within broader cultural and societal contexts, exploring the portrayal of stereotypes and their implications. Findings reveal how humor is derived from exaggeration, absurdity, and reinforcement of stereotypes, particularly regarding Chinese culture, labor practices, and family dynamics. Through structured analysis, the article highlights the nuanced interplay between humor, stereotype, and cultural representation in the context of comedic television. The conclusion underscores the need for critical examination of media portrayals and the importance of understanding the impact of humor on perpetuating or challenging stereotypes. Overall, this study contributes to discourse on racial humor, cultural representation, and media analysis, offering insights into the complexities of comedic storytelling in popular culture.